Accountability and Transparency According to Canon and International Law: A Human Rights Perspective - Beal, John P. (Periodica de re canonica, 2020)
Widely publicized revelations in the summer of 2018 about the sexual abuse of minors by Catholic clergy and the failure of Church authorities to address this abuse adequately placed in a harsh light the deficiencies in structures of accountability in the Church, deficiencies that have been exacerbated by absence of transparency in church governance. Lack of accountability and transparency have, in turn, badly eroded the legitimacy of church governance in the eyes of the public, both Catholic and non-Catholic. Restoration of trust in Church leadership will require developing improved and transparent structures of accountability for Church authorities that engage not only their hierarchical superiors but also the faithful they serve. Lack of transparency in the canonical penal process through which complaints of sexual abuse of minors by clerics are adjudicated have led to complaints of injustice by clerics subjected to the process, victims who often believe their complaints have been ignored or treated as unimportant, and the community of the faithful that is not informed that church authorities have dealt appropriately with complaints of abuse.